2004
DOI: 10.1111/j.1447-0756.2004.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome abnormalities identified in 347 spontaneous abortions collected in Japan

Abstract: Overall patterns of chromosome abnormalities detected in spontaneous abortions in Japan were similar to those reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1
15

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 9 publications
(7 reference statements)
6
62
1
15
Order By: Relevance
“…The spontaneous miscarriage rate is only 3 % in women younger than 30 years old but as high as 29 % in women older than 40 years old [8], and the incidence of chromosomal abnormalities increases from 48 to 65 to 92 % over the same age range [9,10].…”
Section: Advanced Maternal Age (Ma) Is Associated With An Increasedmentioning
confidence: 99%
“…The spontaneous miscarriage rate is only 3 % in women younger than 30 years old but as high as 29 % in women older than 40 years old [8], and the incidence of chromosomal abnormalities increases from 48 to 65 to 92 % over the same age range [9,10].…”
Section: Advanced Maternal Age (Ma) Is Associated With An Increasedmentioning
confidence: 99%
“…Numerical chromosome anomalies are the major cause of recognized early gestational loss, with autosomal trisomies being the most frequent and representing about 50% of all abnormalities, followed by triploidies and monosomy X (Nagaishi et al, 2004;Ljunger et al, 2005). Countless efforts have been made to discover the causes of such cell division errors, particularly in couples presenting recurrence, and several hypotheses to explain them have been proposed (Turleau & Vekemans, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic studies of spontaneous abortions have revealed that chromosome abnormalities are the main cause, contributing with about 50 to 60% of the cases (2,3). Sex chromosome monosomy is the most common chromosomal abnormality in humans, occurring in about 1 to 2% of all pregnancies (4).…”
Section: Introductionmentioning
confidence: 99%